Personality, Stress, and Intuition: Emotion Regulation Abilities Moderate the Effect of Stress-Dependent Cortisol Increase on Coherence Judgments - Radtke, Elise L.; Düsing, Rainer; Kuhl, Julius; Tops, Mattie; Quirin, Markus (Frontiers in Psychology, 2020)
Objective: Findings on the relationship between hypothalamus-pituitary-adrenocortical (HPA) activity and cognitive performance are inconsistent. We investigated whether personality in terms of emotion regulation abilities (ERA) moderates the relationship between stress-contingent HPA activity and intuition. Method: Participants’ (N = 49, aged 18 to 33 years, M = 22.48, SD = 3.33, 32 female) ERA and cortisol responses to social-evaluative stress as induced by a variant of the Trier Social Stress Test were determined. Subsequently, in a Remote Associates Task they provided intuitive judgments on whether word triples, primed by either stress reminding or neutral words, are coherent or not. Results: Under relative cortisol increase participants low in ERA showed reduced performance whereas individuals high in ERA showed increased performance. By contrast, under conditions of low cortisol change, individuals low in ERA showed increased performance compared to individuals high in ERA. Conclusions: ERA can moderate the link between stress and cognition so that existing effects may not be discovered across all individuals, which highlights the necessity to consider individual differences in ERA in stress research, or personality differences in general. We discuss the findings with respect to individual differences in neurobehavioral mechanisms potentially underlying ERA and corresponding interactions with cognitive processing.